Characterization of cassava common mosaic virus and a defective RNA species - Calvert, Lee A.; Cuervo Ibáñez, Maritza; Ospina, M.D.; Fauquet, Claude M.; Ramírez, B.C. (Microbiology Society, 1996)
The genome of cassava common mosaic potexvirus (CsCMV) has been sequenced from cDNA clones and consists of 6376 nucleotides (nt). A 76 nt untranslated region (UTR) at the 5? terminus was followed by ORF1 which potentially encodes a protein of 1449 amino acids (aa). ORFs 2, 3, and 4 were predicted to encode proteins of 231, 112 and 97 aa, respectively. ORF5 potentially encodes a 229 aa protein of 25 kDa that is similar to the coat proteins of other potexviruses. The 3?-terminal UTR of 114 nt was followed by a poly(A) tail. The genomic organization of the CsCMV genome is similar to that of other potexviruses. A cDNA clone that was apparently obtained from a defective RNA species contained both the 5? and 3? UTRs and an ORF that potentially encodes the first 263 aa of ORF1 and the last 33 aa of the coat protein. Defective RNA species were found both in purified preparations of the virus and in total nucleic acid isolated from CsCMV-infected plants.